Housing conditions and coverage of the Family Health Strategy in Brazil: a comparison of the results of the National Health Survey 2013 and 2019 - Wanessa da Silva de Almeida; Célia Landmann Szwarcwald; Paulo Roberto Borges de Souza Júnior
ABSTRACT Objective: This study sought to evaluate information about the characteristics of households and coverage of the Family Health Strategy (FHS), produced in the National Health Survey, and to describe the changes occurred between 2013 and 2019. Methods: Information on households and FHS coverage from the two editions of the National Health Survey (2013 and 2019) was used. Differences between proportions found were assessed, relating to the availability of basic supply and sanitation services, as well as the adequacy of materials used in the building of households, distribution of households' adequacy, and coverage by the FHS according to regions and census situation. The complex sampling design was considered in the analysis, so the t-test for independent samples was used to assess the statistical significance of differences between the proportions found in 2013 and 2019. Results: Upward trends were observed in the percentage of households with adequate finishing, as well as of households with piped water in at least one room, and with adequate basic sanitation (sewage and garbage). The FHS coverage also increased in the period. Regional differences prevail according to urban or rural situation of households. Conclusion: Despite the increases observed both in the adequacy of households, in the availability of basic services and water/sanitation supply and in access to primary health care, many challenges still persist when it comes to ensuring that such services reach the most vulnerable places.